(untitled) (Al-Academy, 2025)
Interior design has historically embraced various changes in form and organization to keep pace with and shape the tradition of structures. A simple invention, a new design attempts to express local culture and available cultural influences by presenting an expressive image of that reality and the associated ideas, perceptions, and values. This is to achieve contemporary design through creative communication and authenticity. This research emphasizes the restoration of the relationship with meaning by adopting a number of innovative concepts and approaches, including the received form. The practical research addresses the use of formalisms that enhance local characteristics in the interior design of cafes in the city of Baghdad, based on a historical tradition of embodying traditional formal names in cafes that summarize development processes. It also addresses the newly established cafes that need to keep pace with this historical heritage, reflecting the richness of local culture and heritage. The research is summarized by the following question: "What are the benefits of local formalisms, and the extent to which they incorporate local Baghdadi characteristics in the design of interior spaces of cafes in Baghdad?" The research aims to reveal the leakage of the employment of the local process, the fastest network of local secretariats of contemporary Baghdad cafes from performance, and the aesthetics of knowledge in order to reach the work while highlighting its authenticity, thought, and cultural and local content. The second chapter deals with two topics: the first: formal profitability in designing interior spaces, the second topic: formal profitability in designing interior spaces for cafes, the third chapter has the research procedures and followed the descriptive research in a quick sample analysis, which "the analysis of two models and the web on the use of the research tool extension using an analysis form in addition to the most important statistical means, where the fourth chapter is a group of the most important: the local Baghdad cafes with all their formal characteristics are nothing but an interaction in the name of the Iraqi designer with his local environment and interact with us, that is, adapting to the place and its influence in addition to the social influences and civilizational factors that teach humanity interacting with its existence, the derivation of the cafe to the outside for the formal, so especially those" spaces in addition to being a means to announce its existence. The research ends with a set of references and then a list of Arabic and foreign sources